KETIDAKFASIHAN BERBICARA DALAM SALURAN â€œPIDATO BAHASA INGGRISâ€ DI YOUTUBE (SUATU ANALISIS PSIKOLINGUISTIK) - Nday, Andre Alfarisman; Jansen, Frieda Th.; Rambing, Rosalina (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2021)
Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â ABSTRACTÂ Â Â Â Â This skripsi entitled Speech Disfluency on â€œEnglish Speechesâ€ Channel at Youtube (A Psycholinguistic Analysis). The thing that we often encounter in speech is disfluency. This disfluency itself occurs due to several factors, both from within and from outside the speaker. The objectives of this research are identify and classify kinds of disfluencies also analyze the factors made speech disfluency on speech videos at Youtube. The writer used Fox-Treeâ€™s (1995) theory for identifying and classifying kinds of disfluencies and used Bortfeldâ€™s, et al. (2001) theory for analyzing the factors made speech disfluencies. The writer used descriptive method in this research. The results of this research indicate that in some of the speech videos studied were found to be more dominant with silent and filled pauses, this is due the factors in the speaker when delivering their speech. Lack of preparation, the large number of audiences, the age of the speaker, the topic of the speech and the enviromental conditions at the time of delivering the speech also have a big effect on the speakerâ€™s disfluency.Keywords: Speech Disfluency, Speech Videos YouTube, Psycholinguistics Analysis